Genomic determinants of specific virulent gene of blastocystis amoeboid stage as a marker in zoonoticpotential, biological and host-parasite relationships - Mohammad, Mardhiah (2019)
Blastocystis sp. is an protozoan with 17 distinctive subtypes discovered in animals and humans worldwide. Unlike human, animal particularly cattle infected with Blastocystis are commonly healthy carriers and serve as a main reservoir in transmiting the infection to human.Thus, this study was aimed to determine the genotypic subtype distribution of Blastocystis sp. of cattle isolated from cattle and protease activities in the selected subtypes. A total of 120 faecal cattle sample were collected from three farms in Pahang, Malaysia for cultivation and microscopy identification. Later, DNA extracted from the faecal were subjected to genotyping analysis before the protease activity of three different subtypes were determined using Azocasein assay.The study found 30 out of 120 (25%) cattle infected with Blastocystis and vacuolar was the dominant morphological forms observed during cultivation. Besides, ST10 occurred predominantly along with another 5 subtypes (ST1, ST3, ST4, ST5 and ST14). Blastocystis ST3, ST5 and ST10 were found to mainly expressed cysteine protease with partially other proteases, which could responsible for the pathogenesis.In conclusion, moderate rates of Blastocystis infection with six different subtypes were identified in the cattle. This information is important in understanding host-parasite relationship associated with protease activity could serve as causative agents for diseases until further investigation were conducted.